Single-component propellant decomposition catalyst accelerated aging test method and application

The oxidation rate of catalyst activated metals is determined through the H2-TPR method, and natural storage data is combined with natural storage to establish accelerated aging test methods to solve the problem of the storage life of catalytic storage quickly in existing technology, and achieve precise estimation of catalyst life. Support for model applications.

CN119335116APending Publication Date: 2025-01-21DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411597579.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

It is difficult to quickly estimate the shelf life of iridium and ruthenium monometallic catalysts in the prior art. The commonly used natural storage test methods cannot be applied due to the long test cycle.

Method used

The oxidation rate of the catalyst activated metal is determined by the H2-TPR method, and the metal oxidation rate in the catalyst is used as the acceleration factor, combined with the naturally stored catalytic oxidation rate change data, to establish an accelerated aging test method, and obtain the aging sample of catalysts that simulate long-term storage.

Benefits of technology

It achieves accurate prediction of catalyst storage life, provides effective basis for catalyst model application, and meets long-term storage and use requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119335116A_ABST
    Figure CN119335116A_ABST
Patent Text Reader

Abstract

The invention provides a single-component propellant decomposition catalyst accelerated aging test method and application, belongs to the technical field of aerospace and aviation catalysts, and is used for rapidly estimating the storage life of iridium and ruthenium monometal catalysts. According to the method, the oxidation rate of active metal of the catalyst is determined through an H2-TPR method, the oxidation state of the catalyst can be accurately controlled by taking the oxidation rate of the metal in the catalyst as an acceleration factor, and an accelerated aging test method is established by combining oxidation rate change data and activity change data of the naturally stored catalyst as references. According to the method, the storage life of the developed catalyst can be effectively estimated, and an effective basis is provided for model application of the catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of aerospace catalysts, and relates to an accelerated aging test method and application of a monocomponent propellant decomposition catalyst, which is mainly used for rapid estimation of the storage life of iridium and ruthenium monometallic catalysts. Background Art

[0002] The monopropellant propulsion system has the advantages of simple structure, sensitive response characteristics, and high working reliability, so it has become the preferred technical solution for equipment terminal power. Green monopropellant propulsion technologies represented by hydrazine catalytic decomposition technology and ADN have been widely used in aerospace and defense fields, such as: anhydrous hydrazine propellant catalytic decomposition technology is applied to satellite and spacecraft attitude and orbit control power systems, single push-3 propellant catalytic decomposition technology is applied to launch vehicles and equipment terminal power systems, and ADN-based AMP-112-I green propellant catalytic decomposition technology is applied to satellite power systems.

[0003] However, as the storage time of the catalyst product increases, the performance of the catalyst will degrade to a certain extent, and even fail. Monocomponent propellant decomposition catalysts are a type of composite inorganic materials with fixed shapes and special functions. They are composed of a carrier and an active metal. The carrier is mainly porous alumina, and the main components of the active metal are precious metals such as Ir and Ru. After a special preparation method, the active metal is highly dispersed on the surface and pores of the carrier at the nanoscale. Unlike single precious metals, nano-dispersed active metals are more active in nature, and therefore exhibit high catalytic activity. At the same time, some storage conditions during long-term storage may also have a certain impact on their lifespan.

[0004] Due to model application requirements, the catalyst needs to be stored for a long time for more than 30 years. Therefore, when developing the catalyst, the storage life of the catalyst must be estimated. However, since the estimated storage life is more than 30 years, the commonly used natural storage test method cannot be applied due to the long test cycle, and the corresponding accelerated aging test method must be developed. Studies have found that highly dispersed active metals will gradually be oxidized by oxygen in the air during long-term storage, resulting in an increase in the oxidation rate of the active metals in the catalyst, resulting in a decrease in activity. Therefore, the oxidation rate of the metal in the catalyst is used as an acceleration factor for experimental design. Summary of the invention

[0005] In order to accurately estimate the storage life of the catalyst, the present invention provides a method and application of accelerating aging test of a monopropellant decomposition catalyst. The present invention measures the oxidation rate of the active metal of the catalyst by the H2-TPR method, takes the metal oxidation rate in the catalyst as the acceleration factor, and combines the data of the change in oxidation rate of the naturally stored catalyst as a reference, which can effectively estimate the storage life of the developed catalyst and provide an effective basis for the model application of the catalyst.

[0006] In order to achieve the above technical tasks, the present invention adopts the following technical solutions:

[0007] A method for accelerated aging test of a monopropellant decomposition catalyst, the test method being: first, establishing a method for detecting the oxidation rate of active metals on a catalyst using H2-TPR; secondly, using the metal oxidation rate detection method, detecting the metal oxidation rate of catalyst materials of different preparation batches or natural storage times, obtaining a fitting formula of storage time-metal oxidation rate, thereby inferring and calculating the metal oxidation rate of the catalyst when it is stored for 20 to 40 years in the future; thirdly, using the metal oxidation rate of the catalyst as an acceleration factor, in order to obtain a catalyst sample with the same oxidation rate as the catalyst when it is stored for 20 to 40 years in the future, an air-heated accelerated aging method is used to accelerate aging of the catalyst, obtaining a fitting formula of aging time-oxidation rate, thereby calculating the aging time when the required specific oxidation rate is reached; fourthly, performing air-heated accelerated aging treatment on the catalyst to obtain a catalyst-aged sample with the same oxidation rate as the inferred storage time; finally, performing a hot test startup test on the catalyst-aged sample to verify whether it can meet the storage and use requirements. Specifically comprising the following steps:

[0008] The first step is to establish a method for detecting the metal oxidation rate of the catalyst using H2-TPR, which specifically includes the following steps:

[0009] Step 1, vacuum drying the test sample until there is no significant change in quality;

[0010] Step 2, weighing about 0.02 g of the sample, placing it in a measuring tube of a chemical adsorption instrument, and installing the measuring tube;

[0011] Step 3, under Ar atmosphere, heating from 50°C to 200°C at a heating rate of 10°C / min, maintaining the temperature at 300°C for 30 min to remove moisture adsorbed in the catalyst, and cooling to room temperature;

[0012] Step 4, using a cold trap device to reduce the sample temperature to -50°C; using 10% H2 / Ar gas (the volume fraction of hydrogen is 10% of the total volume of the two), a flow rate of 10 ml / min, raising the temperature from -50°C to 800°C, and a heating rate of 10°C / min. The thermal conductivity cell records the hydrogen consumption curve during the entire reduction process, and the area integration is performed based on the curve to calculate the hydrogen consumption.

[0013] Step 5, according to the consumption of hydrogen, calculate the amount of reduced metal, combined with the total content of metal on the catalyst, calculate the oxidation rate of the active metal on the catalyst, the calculation method is:

[0014] X = N H2 × M / (2×ω)×100% (1)

[0015] Where: X is the metal oxidation rate in the catalyst; N H2 is the hydrogen consumption measured by H2-TPR, mol / g; M is the atomic mass of the metal, g / mol; ω is the metal content of the catalyst.

[0016] The second step is to detect the metal oxidation rate of catalyst materials of different preparation batches or natural storage times by establishing the catalyst metal oxidation rate detection method in the first step. The sample storage time span is 1 to 2 years, the time point is in months or years, and the measurement points are not less than 3 time points, preferably more than 5 time points. With the storage time as the horizontal coordinate and the metal oxidation rate as the vertical coordinate, curve fitting is performed to obtain the storage time-metal oxidation rate fitting formula. The storage time-metal oxidation rate fitting formula is used for calculation to infer the metal oxidation rate of the catalyst material after 20 to 40 years of natural storage.

[0017] The third step is to use the oxidation rate of the catalyst metal as an acceleration factor. In order to obtain a catalyst sample with the same oxidation rate as the catalyst when stored for 20 to 40 years in the future, the catalyst is aged by accelerating the aging process by heating with air. The method for accelerating the aging of the catalyst specifically includes the following steps:

[0018] Step 1: calibrate the temperature of the constant temperature section of the quartz tube. Fill the quartz tube with quartz sand, as shown in the schematic diagram. Figure 1 As shown, make sure that the thermocouple is located in the middle of the quartz sand. At room temperature, introduce nitrogen / argon with a flow rate of ≥100mL / min and an introduction time of ≥1 hour to replace the atmosphere in the tube with an inert atmosphere. Under an inert atmosphere, set the temperature to the selected temperature, stabilize for 1 to 2 hours, record the constant temperature, observe the difference between the temperature indicated by the detection thermocouple and the set temperature, and reset the temperature until the temperature indicated by the detection thermocouple is the selected temperature ±1°C, thereby determining the accurate set temperature. Move the quartz tube in the tubular furnace, move it inward or outward by about 0.5 to 1 cm, wait for the temperature to stabilize, observe the temperature indicated by the detection thermocouple, if it is within the range of ±2°C of the selected temperature, move it further until it exceeds the range of ±2°C of the selected temperature, thereby determining the constant temperature section of the tubular furnace, and the catalyst must be strictly ensured to be loaded within the constant temperature section.

[0019] Step 2: Load the catalyst sample into a quartz tube. The catalyst loading section is located at the constant temperature section of the treatment tube furnace. Nitrogen / argon is introduced at room temperature with a flow rate of ≥100 mL / min for ≥1 hour to replace the atmosphere in the tube with an inert atmosphere. After the temperature is completely stable at the selected temperature, change to air atmosphere with a flow rate of ≥100 mL / min and start timing.

[0020] Step 3, stop heating, quickly turn off the air, introduce nitrogen / argon at a flow rate of ≥100mL / min to replace the atmosphere in the tube with an inert atmosphere, cool to room temperature, and remove the catalyst.

[0021] According to the above test steps, 100℃, 150℃ or 200℃ is selected as the aging temperature, samples are taken at specific intervals, and the metal oxidation rates of samples with different aging times are detected. With the aging time as the horizontal axis and the metal oxidation rate as the vertical axis, a curve fitting is performed to obtain the aging time-oxidation rate fitting formula. The aging time required for accelerated aging to achieve the same metal oxidation rate as the catalyst with a storage period of 20 to 40 years is calculated using the aging time-oxidation rate fitting formula, thereby obtaining the required catalyst aging samples.

[0022] The fourth step is to age the catalyst according to the aging time obtained in the third step, obtain a catalyst aged sample, and test its oxidation rate to ensure that it is consistent with the oxidation rate of the catalyst during the next 20 to 40 years of storage period estimated in the second step.

[0023] The fifth step is to conduct a hot start test verification on the obtained catalyst aging sample. If it can pass the hot start test verification, it proves that it can meet the storage and use requirements and determines that its storage life is longer than the estimated storage period. If it cannot meet the storage application requirements, it is necessary to reduce the estimated life and conduct a new aging test to finally obtain the corresponding storage life, thereby judging whether it can meet the model requirements.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] The present invention determines the oxidation rate of the active metal of the catalyst by the H2-TPR method, takes the metal oxidation rate in the catalyst as an acceleration factor, and can accurately control the oxidation state of the catalyst by an accelerated aging method; at the same time, combining the storage time of the naturally stored catalyst and the metal oxidation rate data, an accelerated aging test method is established, and an aging sample of the catalyst simulating long-term storage is obtained, which can effectively estimate the storage life of the developed catalyst and provide an effective basis for the model application of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 Schematic diagram of the quartz tube structure for accelerated storage.

[0027] Figure 2 This is a curve diagram of the natural storage time and metal oxidation rate of the Ir / Al2O3 catalyst in Example 1.

[0028] Figure 3 This is a curve diagram of the accelerated aging time of the Ir / Al2O3 catalyst at 200°C and the catalyst metal oxidation rate in Example 1.

[0029] Figure 4This is the startup state curve of the Ir / Al2O3 catalyst in Example 1 after aging.

[0030] Figure 5 This is a curve chart of the natural storage time and metal oxidation rate of the Ru / Al2O3 catalyst in Example 2.

[0031] Figure 6 This is a curve diagram of the accelerated aging time of the Ru / Al2O3 catalyst at 100°C and the oxidation rate of the catalyst metal in Example 2.

[0032] Figure 7 This is the startup state curve of the Ru / Al2O3 catalyst in Example 2 after aging. DETAILED DESCRIPTION

[0033] The following are examples provided by the inventor to further explain this test method:

[0034] Embodiment 1:

[0035] The test sample is Ir / Al2O3 catalyst material, in which the Ir content is 17%, and it has been naturally stored for about 10.8 years. The H2-TPR test results of the metal oxidation rate of the sample catalyst with different storage times are shown in Table 1. The storage time is taken as the horizontal axis (year) and the metal oxidation rate (%) is taken as the vertical axis. The curve fitting is performed to obtain the following: Figure 2 From the curve shown and the fitting formula: y=0.7758x+47.3532, it can be inferred that when the storage time reaches 20 years, the metal oxidation rate of the catalyst is 62.8683%.

[0036] The aging temperature was 200°C, and the metal oxidation rate at different aging times was measured at intervals of 30 minutes. The experimental data are shown in Table 2. With the aging time as the horizontal axis and the metal oxidation rate as the vertical axis, curve fitting was performed to obtain the following: Figure 3 The curve and fitting formula shown are:

[0037] Accelerated aging time < 0.5 hours: y = 17.4709x + 47.8575

[0038] Accelerated aging time>0.5 hours: y=3.8546x+54.8090

[0039] According to the above formula, the aging time required to achieve a metal oxidation rate of 62.8683% is 2.09 hours. The sample was aged for 2.09 hours, and its oxidation rate data is shown in Table 2, which is 62.91%, which is basically consistent with the estimate.

[0040] The catalyst start-up activity test was carried out on the sample, and the test results were as follows: Figure 4As shown, it can complete the startup conditions well and meet the startup requirements, indicating that the catalyst can meet the storage applicability requirements for 20 years.

[0041] Table 1 Data of natural storage catalyst and catalyst oxidation rate

[0042]

[0043] Table 2 Data of catalysts and catalyst oxidation rates at different accelerated aging times

[0044]

[0045]

[0046] Embodiment 2:

[0047] The test sample is a Ru / Al2O3 catalyst material with a Ru content of 24%. It has been naturally stored for about 32 months. The H2-TPR test results of the metal oxidation rate of the sample catalysts with different storage times are shown in Table 3. The storage time is taken as the horizontal axis (year) and the metal oxidation rate (%) is taken as the vertical axis. The curve fitting is performed to obtain the following: Figure 5 The curve and fitting formula shown are:

[0048] Storage time ≤ 14 months, y = 1.1743x + 35.6000

[0049] Storage time>14 months, y=0.0661x+51.2261

[0050] It can be inferred that when the storage time reaches 30 years, the metal oxidation rate of the catalyst is 75.0621%.

[0051] The aging temperature was 100°C, and the metal oxidation rate at different aging times was measured at intervals of 30 minutes. The experimental data are shown in Table 4. With the aging time as the horizontal axis and the metal oxidation rate as the vertical axis, curve fitting was performed to obtain the following: Figure 6 The curve and fitting formula shown are:

[0052] Accelerated aging time <1 hour: y = 5.8812x + 35.6000

[0053] Accelerated aging time 1 to 9 hours: y = 2.1398x + 38.7705

[0054] Accelerated aging time>9 hours: y=0.4369x+55.5827

[0055] According to the above formula, the aging time required to achieve a metal oxidation rate of 75.0621% is 44.59 hours. The sample was aged for 44.59 hours, and its oxidation rate data is shown in Table 4, which is 75.20%, which is basically consistent with the estimate.

[0056] The catalyst start-up activity test was carried out on the sample, and the test results were as follows: Figure 7 As shown, it can complete the startup conditions well and meet the startup requirements, indicating that the catalyst can meet the storage applicability requirements for 30 years.

[0057] Table 3 Natural storage catalyst and catalyst oxidation rate data

[0058]

[0059] Table 4 Data of catalysts and catalyst oxidation rates at different accelerated aging times

[0060]

[0061] The above-described embodiments merely express the implementation methods of the present invention, but they cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that for those skilled in the art, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A method for accelerating aging test of monopropellant decomposition catalyst, characterized in that: The test method is as follows: first, a method for detecting the oxidation rate of active metals on a catalyst using H2-TPR is established; second, the metal oxidation rate of different catalyst materials is detected by the metal oxidation rate detection method to obtain a fitting formula of storage time-metal oxidation rate, thereby inferring and calculating the metal oxidation rate of the catalyst when it is stored for N years in the future; third, the metal oxidation rate of the catalyst is used as an acceleration factor, and in order to obtain a catalyst sample with the same oxidation rate as the catalyst when it is stored for N years in the future, the catalyst is accelerated to age, and the fitting formula of aging time-oxidation rate is obtained, thereby calculating the aging time when the required specific oxidation rate is reached; Fourth, the catalyst is subjected to air-heated accelerated aging treatment to obtain a catalyst-aged sample with the same oxidation rate as the inferred storage time; finally, a hot start-up test is performed on the catalyst-aged sample to verify whether it can meet the storage and use requirements.

2. The accelerated aging test method for a monopropellant decomposition catalyst according to claim 1, characterized in that: The specific steps include: The first step is to establish a method for detecting the metal oxidation rate of the catalyst using H2-TPR, comprising the following steps: Step 1.1, vacuum drying the test sample until there is no significant change in mass; Step 1.2, placing the test sample in the measuring tube of the chemical adsorption instrument and installing the measuring tube; Step 1.3, under Ar atmosphere, heat from 50°C to 200°C, keep constant at 300°C for 30 min, and then cool to room temperature; Step 1.4, using a cold trap device to reduce the sample temperature to -50°C; using H2 / Ar gas, heating from -50°C to 800°C, and using a thermal conductivity cell to record the hydrogen consumption curve during the entire reduction process, and calculating the hydrogen consumption by performing area integration based on the curve; Step 1.5, calculating the amount of reduced metal based on the hydrogen consumption, and calculating the oxidation rate of the active metal on the catalyst based on the total metal content on the catalyst; The second step is to detect the metal oxidation rate of the catalyst materials of different preparation batches or natural storage times by establishing the catalyst metal oxidation rate detection method in the first step, the sample storage time span is 1 to 2 years, the time point is in months or years, and the measurement points are not less than 3 time points; with the storage time as the horizontal axis and the metal oxidation rate as the vertical axis, curve fitting is performed to obtain the storage time-metal oxidation rate fitting formula; the storage time-metal oxidation rate fitting formula is used for calculation to infer the metal oxidation rate of the catalyst material after 20 to 40 years of natural storage; The third step is to use the catalyst metal oxidation rate as an acceleration factor, and to accelerate the aging of the catalyst by using an air heating accelerated aging method in order to obtain a catalyst sample with the same oxidation rate as the catalyst when stored for 20 to 40 years in the future; the steps include: Step 3.1, calibrate the temperature of the constant temperature section of the quartz tube; fill the quartz sand into the quartz tube; introduce nitrogen / argon at room temperature to replace the atmosphere in the tube with an inert atmosphere; under the inert atmosphere, set the temperature to the selected temperature, stabilize for 1 to 2 hours, record the constant temperature, observe the difference between the temperature indicated by the detection thermocouple and the set temperature, and reset the temperature accordingly until the temperature indicated by the detection thermocouple is the selected temperature ±1°C, thereby determining the accurate set temperature; move the quartz tube in the tube furnace, move it inward or outward by 0.5 to 1 cm, wait for the temperature to stabilize, observe the temperature indicated by the detection thermocouple, if it is within the range of ±2°C of the selected temperature, move it further until it exceeds the range of ±2°C of the selected temperature, thereby determining the constant temperature section of the tube furnace; ensure that the catalyst is loaded in the constant temperature section; Step 3.2, the catalyst sample is loaded into a quartz tube, the catalyst loading section is located at the constant temperature section of the treatment tube furnace, nitrogen / argon is introduced at room temperature, and the atmosphere in the tube is replaced with an inert atmosphere; after the temperature is completely stable at the selected temperature, the atmosphere is changed to air, the flow rate is ≥100mL / min, and the timing is started; Step 3.3, stop heating, quickly turn off the air, introduce nitrogen / argon, replace the atmosphere in the tube with an inert atmosphere, cool to room temperature, and take out the catalyst; According to the above test steps, 100°C, 150°C or 200°C is selected as the aging temperature, samples are taken at specific intervals, and the metal oxidation rates of samples with different aging times are detected; with the aging time as the abscissa and the metal oxidation rate as the ordinate, a curve fitting is performed to obtain an aging time-oxidation rate fitting formula; the aging time required for accelerated aging to achieve the same metal oxidation rate as the catalyst with a storage period of 20 to 40 years is calculated using the aging time-oxidation rate fitting formula, thereby obtaining the required catalyst aging samples; The fourth step is to age the catalyst according to the aging time obtained in the third step, obtain an aged catalyst sample, and test its oxidation rate to ensure that it is consistent with the oxidation rate of the catalyst during the next 20 to 40 years of storage period inferred in the second step; The fifth step is to conduct a hot start-up test on the obtained catalyst aging sample. If it can pass the hot start-up test, it proves that it can meet the storage and use requirements and determines that its storage life is longer than the estimated storage period. If it cannot meet the storage applicability requirements, it is necessary to reduce the estimated life and conduct a new aging test to finally obtain the corresponding storage life, thereby judging whether it can meet the requirements.

3. The accelerated aging test method for a monopropellant decomposition catalyst according to claim 2, characterized in that: In the step 1.3, the heating rate is 10°C / min; in the step 1.4, the heating rate is 10°C / min; the flow rate of the H2 / Ar gas is 10 ml / min, and the volume fraction of hydrogen in the H2 / Ar gas is 10%.

4. The accelerated aging test method for a monopropellant decomposition catalyst according to claim 2, characterized in that: In the step 1.5, the oxidation rate of the active metal on the catalyst is calculated as follows: X = N H2 × M / (2×ω)×100% (1) Where: X is the metal oxidation rate in the catalyst; N H2 is the hydrogen consumption measured by H2-TPR, mol / g; M is the atomic mass of the metal, g / mol; ω is the metal content of the catalyst.

5. The accelerated aging test method for a monopropellant decomposition catalyst according to claim 2, characterized in that: In the step 3.1, the flow rate of nitrogen / argon is ≥100 mL / min, and the introduction time is ≥1 hour.

6. The accelerated aging test method for monopropellant decomposition catalyst according to claim 2, characterized in that: In the step 3.2, nitrogen / argon is introduced at a flow rate of ≥100 mL / min and for a time of ≥1 hour.

7. The accelerated aging test method for monopropellant decomposition catalyst according to claim 2, characterized in that: In the step 3.2, nitrogen / argon is introduced at a flow rate of ≥100 mL / min.

8. An application of the accelerated aging test method for monopropellant decomposition catalyst according to any one of claims 1 to 7, characterized in that: Applied to the estimation of storage life of iridium and ruthenium monometallic catalysts.